Development of Interactive Media Based on Application Assisted by Claude AI in Physical Education Subjects for Elementary Schools - Arindra Yudhianto; Achmad Noor Fatirul; Hartono (Poltanesa, 2025)
The learning process in Physical Education (PE) at the elementary school level still relies on conventional approaches and lacks the use of technology that supports health assessment activities. This research aims to develop an interactive learning media application assisted by Claude AI to help fifth-grade students conduct simple health checks, including eye, ear, oral, and body mass index (BMI) assessments. This study employed the ADDIE development model, consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. The subjects involved 5 students in a small trial, 15 students in a limited trial, and 30 students in a large group trial. Additionally, 30 validators consisting of material experts, media experts, and design experts assessed the feasibility of the product. Data were collected through expert validation sheets, student response questionnaires, and pretest–posttest instruments. The results showed that the media achieved a very high feasibility level, with design experts scoring 95.9%, material experts 98.5%, and media experts 94.2%. Student response results also indicated high practicality, with scores of 80.7% in the limited trial and 89.5% in the large group trial. the application proved effective in improving students’ understanding, as demonstrated by an average N-gain score of 0.79 in the high category. These findings indicate that Claude AI–assisted interactive media is feasible, practical, and effective as a learning innovation that supports health literacy and enhances PE learning in elementary schools.